Serious games for seniors: learning safe behaviors on the web - Bernardino, Iolanda (2021)
In a modern society, seniors want to be a part of the digital world and the research in progress seeks to present whether through Serious Games can help their learning process and understanding of cybersecurity when online browsing, namely, deciding which actions to make when facing an eminent threat.